2016
DOI: 10.1097/wno.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Myelogenous Leukemia Relapse Presenting With Central Nervous System Blast Crisis and Bilateral Optic Nerve Infiltration

Abstract: Bilateral, simultaneous optic nerve sheath infiltration as a manifestation of leukemia relapse is very rare. A 45-year-old woman with chronic myelogenous leukemia was successfully treated to cytogenetic bone marrow remission 1 year previously and maintained on imatinib. She developed total bilateral blindness with marked, bilateral optic disc edema and evidence of bilateral optic nerve infiltration on magnetic resonance imaging. Cerebrospinal fluid cytology confirmed central nervous system (CNS) blast crisis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…About imaging findings, there have been some studies on hematological malignancies such as leukemia and lymphoma invading the CNSL [12][13][14], but seldom on AML. In order to solve this problem, we summarized the MRI manifestations of AML complicated with CNSL, which contributes to the improvement of diagnostic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…About imaging findings, there have been some studies on hematological malignancies such as leukemia and lymphoma invading the CNSL [12][13][14], but seldom on AML. In order to solve this problem, we summarized the MRI manifestations of AML complicated with CNSL, which contributes to the improvement of diagnostic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A previous case reported complete remission of patients with chronic myeloid leukemia relapse presenting with CNS blast crisis and bilateral optic nerve infiltration after systemic, intrathecal chemotherapy, radiation, and allogeneic hematopoietic stem-cell transplantation. [ 23 ] Although our patients received a significant response, we acknowledge that leukemia cells in the space surrounding the nervous system are not completely eliminated. We recommend radiation therapy and allogeneic hematopoietic stem-cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…1 Mbekeani et al reported a case of a 45-year-old woman with CML who developed bilateral no-light-perception vision with optic disc edema, and the MRI confirmed optic nerve infiltration. 2 Schocket et al described a case of 58-year-old man with CML of 5 years' duration who presented with painless, progressive left eye vision loss. A contrast MRI showed no enhancement of the optic nerves, but there was subtle enhancement of cranial nerves VII and VIII suggestive of leptomeningeal involvement.…”
Section: Optic Neuropathy In Extramedullary Blast Crisis Of Chronic mentioning
confidence: 99%